Biomechanics : principles, trends and applications - Levy, Jerrod H. (Biomechanics : Theory and Applications., 2010)
"Biomechanics is the application of mechanical principles (statics, strength of materials and stress analysis to the solution of biological problems of living organisms. This includes bioengineering, the research and analysis of the mechanics of living organisms and the application of engineering principles to and from biological systems. This research and analysis can be carried forth on multiple levels, from the molecular, wherein biomaterials such as collagen and elastin are considered, all the way up to the tissue and organ level. This new and important book gathers the latest research from around the globe in the study of this dynamic field with a focus on issues such as; art biomechanics, understanding corneal biomechanics, biomechanical remodeling of the diabetic gastrointestinal tract, biomechanics in children with cerebral palsy, cell biomechanics for orthopaedic implants, and others."--Publisher's description.